ETHOPHARMACOLOGICAL ANALYSIS OF RAT BEHAVIOR ON THE ELEVATED PLUS-MAZE - Cruz, APM; Frei, F.; Graeff, F. G. (Elsevier B.V., 1994)
Behavioral categories were measured in rats left on an elevated plus-maze for 5 min, in addition to the traditional measures. Four independent factors emerged from a factor analysis. The variables that loaded highly and positively on Factor 1, seemingly related with anxiety, were: number of entries onto open arms, time spent on open arms, percentage of open/total arm entries, percentage of time on open arms, scanning over the edge of an open arm, and open arm end-exploring. The time spent on enclosed arms loaded highly, but negatively on the same factor. Risk-assessment from an enclosed arm also loaded negatively on Factor 1. Number of enclosed arm entries, total number of arm entries and rearing loaded highly on Factor 2, probably related to motor activity. However, the total number of entries also loaded on Factor 1, being thus a mixed index. Similarly, the number of open arm entries loaded on both Factors 1 and 2. As expected, the variables having high loads on Factor 1 were changed to one direction by administration of two anxiolytics (nitrazepam and midazolam) and to the opposite direction by two anxiogenic drugs (pentylenetetrazol and FG 7142). Such pattern of drug effects was not observed with the remaining variables.
Keywords: ELEVATED PLUS-MAZE; RATS; FACTOR ANALYSIS; ANXIOLYTICS; ANXIOGENIC DRUGS